Pertinence of Apoptosis Markers for the Improvement of In Vitro Fertilization (IVF) - Haouzi, D.; Hamamah, S. (Current Medicinal Chemistry, 2009)
In assisted reproductive technology (ART), the pregnancy and birth rates following in vitro fertilization (IVF) attempts are still low. Recently, apoptotic markers have been suggested as new criteria for oocyte and embryo quality selection. Many studies have provided evidence that poor oocyte and embryo quality can be associated with apoptosis. The aim of this review is to summarize our current knowledge on the apoptotic process in oocytes and embryos, and focus on the possibility for using apoptotic markers as a reliable and predictive marker to select competent oocytes and embryos during IVF. Moreover, it is currently accepted that IVF failures, linked to poor embryo quality, are, in part, associated with suboptimal in vitro culture conditions. Here, we also review the current state of knowledge concerning how the genetic control of apoptosis during folliculogenesis and pre-implantation embryonic development is affected by in vitro culture conditions during IVF. In the future, identification of apoptotic markers in ART for oocyte and embryo selection should result in the development of new agonistic or antagonistic molecules of apoptosis by medicinal chemistry.
Keywords: apoptosis markers